Optimization of Primer Candidate Design for Toxocara cati Identification Using PCR Targeting the COX1 and ND5 Genes in Cats - Yesica, Reza; Novita, Ni Kadek; Kusumarini R, Shelly; Sabri, Jasni (Jurnal Medik Veteriner, 2025)
Toxocara cati is an obligate extracellular parasite within the phylum Nematoda. This species is responsible for toxocariasis, a zoonotic disease. The disease transmission occurs via infective eggs, earthworms, cockroaches, birds, and rodents that contain larvae in their tissues. In cats, infection with this parasite can lead to symptoms such as diarrhea, hypoalbuminemia, anorexia, and a distended abdomen. This research aimed to identify an optimal candidate primer design through in silico analysis using BLAST primers from the National Center for Biotechnology Information (NCBI). This study targeted the mitochondrial genes COX1 and ND5 for the molecular identification of T. cati. Using in silico methods, primer candidates were designed and evaluated based on key parameters, including primer length, melting temperature (Tm), GC content, potential for secondary structure formation, and specificity. Candidate primers were screened using the NCBI primer-BLAST tool and validated through BLAST analysis to ensure sequence specificity. The primer pair that met all the criteria for an optimal candidate primer design comprised the forward primer TCND5F (5′-ACTGCTGGCCTTGTATTGGT-3′) and the reverse primer TCND5R (5′-ACACAGAACGCCTAAACCTCA-3′), both targeting the ND5 gene region.